West-Eastern Poetic Compositions of the First Third of the 19th Century: from Goethe’s Divan to the ‘Sonnet/Ghazal’ by Mickiewicz/Topczi-Baszy - Alexander B. Kudelin (Studia Litterarum)
The article is concerned with reciprocity between Western and Eastern literatures of the 19th century, when Orientalist motives began to take hold in European writings. Goethe, in his “West-Östlicher Divan” (1819), attributed this interest to the everlasting excellence and value, which the Eastern masterpieces hold for the West. However, as it is clear nowadays, the ‘West-Eastern’ compositions cannot be seen as truthfully retaining the spirit of the Eastern classics, which was based on a different system of meanings and values. On the other hand, it became clear that the Eastern reception of these European works in the 19th century could not be true to the Western original, either, since even most progressive Eastern literatures of the time kept to artistic principles and system of genres of the Late Middle Ages. Against this historical and critical background, the article investigates the outcome of one venture — the emergence of a Persian translation of Adam Mickiewicz’s poem, commissioned by himself for his “Sonnets” (1826). Dzafar Topczi-Baszy adjusted the sonnet for an Eastern audience. Having presented his translation as a sample of the medieval genre of tadhkira (which has to contain both biographical and anthological features), Topczi- Baszy supplied the Persian version of the poem with facts about Mickiewicz; he cast the poem into a Persian poetic form — ghazal; he replaced the elements of Romantic imagery with the Eastern ones.